2021
DOI: 10.3390/antiox10050731
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondria-to-Cytosol H2O2 Gradient Is Caused by Peroxiredoxin-Dependent Cytosolic Scavenging

Abstract: Fluorescent protein-based reporters used to measure intracellular H2O2 were developed to overcome the limitations of small permeable dyes. The two major families of genetically encoded redox reporters are the reduction-oxidation sensitive green fluorescent protein (roGFP)-based proteins fused to peroxiredoxins and HyPer and derivatives. We have used the most sensitive probes of each family, roGFP2-Tpx1.C169S and HyPer7, to monitor steady-state and fluctuating levels of peroxides in fission yeast. While both ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…We found that the cytoplasmic HyPer sensor is fully reduced in cells with normal metabolism suspended in a complete growth medium. These observations are consistent with the already published research [ 22 ] but differ from our previously obtained data related to K-562 cells suspended in PBS [ 12 ]. According to [ 12 ], HyPer is slightly oxidized (∼10%) under such conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the cytoplasmic HyPer sensor is fully reduced in cells with normal metabolism suspended in a complete growth medium. These observations are consistent with the already published research [ 22 ] but differ from our previously obtained data related to K-562 cells suspended in PBS [ 12 ]. According to [ 12 ], HyPer is slightly oxidized (∼10%) under such conditions.…”
Section: Discussionsupporting
confidence: 90%
“…(2) ) that the sensor can be fully oxidized only under the condition of , i.e. at complete oxidation of thiol-disulfide exchange enzymes which are responsible for the HyPer redox-active domain reduction (presumably, thioredoxin system [ 10 , 22 , 23 ]). Correspondingly, we suggested that it is the functional status of the thioredoxin-depended enzymatic system that drives the dependence of the H 2 O 2 gradient on the oxidative load.…”
Section: Discussionmentioning
confidence: 99%
“…To uncover the consequences of these alterations of the OXPHOS system, we measured H 2 O 2 abundance at the mitochondrial matrix by expressing the peroxide reporter HyPer7 at this subcellular compartment and determining its oxidation levels [ 27 , 28 ]. The percentage of oxidation of this reporter depends on the steady-state H 2 O 2 levels at the matrix, being around 40% (OxD 0 of 0.4) in wild-type cells and increasing up to 60% when the main H 2 O 2 scavenger, Tpx1, is missing [ 28 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of plasmid construction and the experimental procedure has been published [ 28 ]. Briefly, plasmid p730 carrying the reporter HyPer7 with the MTS (mitochondrial targeting sequence) of Aco1 was transformed in the mitochondrial protease mutants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation